2003
DOI: 10.1128/jvi.77.20.11050-11059.2003
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Chimeric Human Immunodeficiency Virus Type 1 (HIV-1) Containing HIV-2 Integrase (IN): Naturally Selected Mutations in IN Augment DNA Synthesis

Abstract: Human immunodeficiency virus type 1 (HIV-1) encodes protease (PR), reverse transcriptase (RT), and integrase (IN) as parts of a large Gag-Pol precursor polyprotein (Pr160 Gag-Pol ). Pr160 Gag-Pol plays an important role in virion assembly and is essential for the formation of infectious virions (for a review, see reference 11). Mutagenesis of the C-terminal region of Pr160Gag-Pol (RT and IN domains) has been associated with defects in virion assembly, release, maturation, and protein composition (2,4,7,8,26,31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…To assess whether the effect of p21 on HIV-1 replication was virus specific, we studied the infectivity of SIVmac-251, a dual tropic (T- and M-tropic) lentivirus related to HIV-1 (29)(30)(31), in both p21 siRNA-treated primary cells and in CMK cells. A low level of viral antigen p27 was detected (0.103 ± 0.001 ng/ml) in culture supernatant of CD34 + cells at day 7, but this dropped to background levels by day 10 (<0.05 ng/ml; Figure 7A).…”
Section: Inhibition Of Hiv-1 Infection Is Specific and Independent Ofmentioning
confidence: 99%
“…To assess whether the effect of p21 on HIV-1 replication was virus specific, we studied the infectivity of SIVmac-251, a dual tropic (T- and M-tropic) lentivirus related to HIV-1 (29)(30)(31), in both p21 siRNA-treated primary cells and in CMK cells. A low level of viral antigen p27 was detected (0.103 ± 0.001 ng/ml) in culture supernatant of CD34 + cells at day 7, but this dropped to background levels by day 10 (<0.05 ng/ml; Figure 7A).…”
Section: Inhibition Of Hiv-1 Infection Is Specific and Independent Ofmentioning
confidence: 99%
“…It has also been proposed that the active form of the yeast Saccharomyces cerevisiae retrotransposon Ty3 RT is an ␣/␤ heterodimer (27). In other retroviruses, RT and IN are fully separated by proteolytic processing during virion maturation, but mutations or deletions in the nonconserved domain of IN affect several stages of viral replication other than integration, including the initiation of reverse transcription, the level of cDNA, 3Ј-end DNA processing, or nuclear entry (19,28,40,43). Coimmunoprecipitation experiments with antibodies to RT or IN have demonstrated that the human immunodeficiency virus type 1 (HIV-1) or murine leukemia virus proteins interact physically in vitro (16,17,32).…”
mentioning
confidence: 99%
“…Increasing evidence suggests that functional and physical interactions between these two enzymes occur during replication (15,28,40,43). In some retroviruses IN is an integral part of the active enzyme; it is an ␣/␤ heterodimer composed of a short RT (␣) polypeptide and an incompletely processed RT-IN (␤) intermediate in the avian leukosis viruses (18,36) and an oligomer of the ␣3/␤ type in human T-cell leukemia virus type 1 (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gag-Pol (35,49,50). In this report, we describe a novel trans-complementation approach that enables the function of each RT subunit to be studied in the context of an infectious virus.…”
mentioning
confidence: 99%